The economic implications of the housing problem In Iraq and ways to address it - a theoretical research - motar, Fareq cheid; Salman Al-Kubaisi, Mohammed Saleh (Journal of Economics and Administrative Sciences, 2020)
The problem of housing in Iraq is a long-rooted and rooted problem, and it needs a great effort to find out its causes and thus give essential points that contribute to alleviating and addressing it, and it is worth noting that research into the housing problem and the housing sector in Iraq is not done in isolation from other sectors and studies. As well as the economic policies pursued and the social and political conditions. It is known that the Iraqi economy is a unilateral (rentier) economy, that is, it depends almost entirely on exporting oil and obtaining revenues, and that the economic decision and economic policies followed in Iraq are greatly affected by several factors, including the economic, social and political factor, and this led to structural imbalances And many economic problems need continuous efforts to sort and arrange them and then reconfigure them again, and this matter calls for studying the Iraqi economy in detail with a focus on the many problems that its economy suffers from, especially the housing problem, in order to analyze and know the reasons that led to its emergence, as well as the result that brought To avoid these problems in the future.